MENINGKAKAN KEMAMPUAN MOTORIK HALUS ANAK USIA DINI MELALUI KEGIATAN MEWARNAI GAMBAR DI PAUD AL-MUZDALIFAH - Hulaelah; Mutoharoh; Euis Rusmala; Budi Ilham Maliki; Siti Kholifah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The problem in this study is the low development of fine motor skills in early childhood. This study aims to improve fine motor skills in early childhood through coloring activities. This research is motivated by the low level of fine motor skills in students, which impacts learning outcomes. Students who should have begun to be able to hold a pencil well, but at PAUD BKB Al-Muzdalifah still have difficulty holding a pencil. Therefore, the researcher provides a solution to improve fine motor skills in early childhood through coloring activities. This study is a classroom action research using two cycles of three meetings. Data collection techniques used observation, documentation, and data analysis. The results obtained an average increase in fine motor skills in each meeting using coloring activities. From this study, it can be concluded that there is an increase in fine motor skills in early childhood through coloring activities.